Analgesic Effect of Bangle Rhizome Ethanol Extraction on Thermally Induced Pain in Mus musculus - Pangkerego, Margareth Ayu Caroline; Hamzah, Hamzah; Indiastuti, Danti Nur (Biomolecular and Health Science Journal, 2019)
Introduction: Pain causes deterioration of quality of life. Nonsteroidal anti-inflammatory drug (NSAID) is used to relieve pain with upper gastrointestinal side effects. Zingiber cassumunar Roxb. (known as bangle) is commonly used to relieve pain, but no study has been proved to have analgesic effect. In empirical study, bangle is a potential analgesic due to its bioactive compound named zerumbone. The aim of this study was to investigate the analgesic effect of bangle rhizome ethanol extraction on thermally induced pain.Methods: Five groups of male Mus musculus consisting of 6 mice each were used. A single dose of bangle extract 2 mg/20 g, 4 mg/20 g, 8 mg/20 g, aspirin 1.82 mg/20 g, and aquadest 0.2 ml were administrated. The analgesic effect was evaluated by hot plate test. The test was evaluated at 15th, 30th, 45th minute. Latency period was observed when mice showed pain responses including hind paw shaking, hind paw licking or jumping. The data was analyzed by paired T-test and one-way ANOVA.Results: Results showed that all doses of bangle extract and aspirin 1.82 mg/20 g produced significant latency period (p<0.05) compared to baseline in each group using paired T-test. Latency period of bangle extract 8 mg/20 g was more significant than bangle extract 2 mg/20 g and 4 mg/20 g. One-way ANOVA showed no significant difference in latency period (p=0.1) between bangle extract and aspirin (p>0.05).Conclusion: Bangle extract has analgesic effect on thermally induced pain. The minimum dose for analgesic is 2 mg/20 g or potentially less.